The use of foreign currency derivatives, exchange rate exposure, and firm value - Liu, Zhi-jia (2022)
This dissertation mainly examines whether the use of foreign currency derivatives can positively affect the firm value in a sample of 124 firms from the S&P 500 in the US. I examine the relationship between hedging and exposure of exchange rate, suggesting the existence of a negative association. Theories of hedging claim that the use of derivatives can reduce the various costs caused by market imperfection. A fixed-effect model is established to examine the value-adding effect of foreign currency derivatives on the firms. I verify that the extent of the use of foreign currency derivatives is positively associated with corporate value. In addition, I find that the companies with strong corporate governance have higher hedge premiums, indicating that the governance quality of the firms could affect the effectiveness of hedging. The use of foreign currency derivatives may fluctuate over time according to macro-economic reasons. I also find that the value-enhancing effect of the foreign currency usage is still significant during the Covid-19 crisis for the sample companies.